Recent advances in the regulatory and non-coding RNA biology of osteogenic differentiation: biological functions and significance for bone healing - Aranguren, Samaris; Cole, Hisae; Dargan, Lauren Jeannette; Sarlo, Madison; Choi, Sumin; Satapathy, Isha; de Vasconcellos, Jaira Ferreira (Frontiers in Cell and Developmental Biology, 2025)
Injuries associated with contemporary life, such as automobile crashes and sports injuries, can lead to large numbers of traumatic neuromuscular injuries that are intimately associated with bone fractures. Regulatory and non-coding RNAs play essential roles in multiple cellular processes, including osteogenic differentiation and bone healing. In this review, we discuss the most recent advances in our understanding of the regulatory and non-coding RNA biology of osteogenic differentiation in stem, stromal and progenitor cells. We focused on circular RNAs, small nucleolar RNAs and PIWI-interacting RNAs and comprehensively summarized their biological functions as well as discussed their significance for bone healing and tissue regeneration.